STUDENTS’ PERSPECTIVES ON THE TEACHERS’ WRITTEN CORRECTIVE FEEDBACK IN ONLINE PROFESSIONAL NARRATIVE WRITING CLASS - Sukha, Prema Gupita; Listyani, Listyani (LLT Journal: A Journal on Language and Language Teaching, 2022)
This research aimed to find out students' perspectives on the teachers' written corrective feedback in online Professional Narrative Writing classes and discover the types of the teachers' written corrective feedback that Professional Narrative Writing students prefer to help them revise their writing. Thus, the research questions of this study were (1) What are the students' perspectives on the teachers' written corrective feedback in online Professional Narrative Writing class? and (2) What are the types of the teachers' written corrective feedback that the students prefer to get to help them revise their writing in Professional Narrative Writing class? The participants of this study were thirty-four (34) students from three online Professional Narrative Writing classes in Universitas Kristen Satya Wacana. This study was conducted from September until December 2021. Also, the data collection instruments used open-ended and closed-ended questionnaires and interviews. The findings showed that the participants had positive and negative perspectives toward the teachers' written corrective feedback in online Professional Narrative Writing class. Then, the most preferred type of the teachers' written corrective feedback was indirect feedback since the participants believed it could help them revise their essays. Therefore, the findings of this study were expected to be useful for teachers in giving effective written corrective feedback.  Keywords: students' perspectives, the teachers' written corrective feedback, online professional narrative writing class